2014
DOI: 10.1111/aor.12319
|View full text |Cite
|
Sign up to set email alerts
|

A New Computational Fluid Dynamics Method for In‐Depth Investigation of Flow Dynamics in Roller Pump Systems

Abstract: Roller pumps are commonly used in circulatory assist devices to deliver blood, but the inherent high mechanical stresses (especially wall shear stress) may cause considerable damage to cells. Conventional experimental approaches to evaluate and reduce device-induced cell damage require considerable effort and resources. In this work, we describe the use of a new computational fluid dynamics method to more effectively study roller pump systems. A generalized parametric model for the fluid field in a typical rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The present study showed that high pulsatility does not exist at the arterial needle due to the counteracting force of blood pressure and the compressibility of the tubing indi- Microemboli have been reported to enter the circulation and deposit in the lungs and brain which can cause tissue ischemia and neurological conditions (8)(9)(10). A computational optimization of a roller pump has shown that increasing the number of rollers can produce more uniform and steady flow conditions and reduces the instantaneous maximum velocity (21). It is therefore imperative to determine the source, and implement methods to prevent their passage through the extracorporeal circuit and into the patient.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The present study showed that high pulsatility does not exist at the arterial needle due to the counteracting force of blood pressure and the compressibility of the tubing indi- Microemboli have been reported to enter the circulation and deposit in the lungs and brain which can cause tissue ischemia and neurological conditions (8)(9)(10). A computational optimization of a roller pump has shown that increasing the number of rollers can produce more uniform and steady flow conditions and reduces the instantaneous maximum velocity (21). It is therefore imperative to determine the source, and implement methods to prevent their passage through the extracorporeal circuit and into the patient.…”
Section: Discussionmentioning
confidence: 64%
“…It is this phenomenon that causes the extracorporeal tubing to pulse. This instantaneous flow reversal has previously been visualized in a fluid-structure simulation (21). The venous air trap is the most effective mechanism in the circuit at removing this pulse.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A long-term animal study is required to assess whether there is any potential for valve damage. Thrombosis in the RJV after use of the Avalon Elite has been reported 31 . Although this thrombosis may be removed by a minor surgery during DLC withdrawal 31 , this potential drawback may dampen enthusiasm for the pRVAD DLC since the RJV is a frequent site for endomyocardial biopsies following heart transplant.…”
Section: Discussionmentioning
confidence: 99%
“…This effect as a function of the length-to-thickness ratio. It has been noted by different authors [25][26][27][28] that the transverse shear effect:…”
Section: Testingmentioning
confidence: 99%